2013
DOI: 10.1111/trf.12190
|View full text |Cite
|
Sign up to set email alerts
|

Head‐to‐head comparison of two transcription‐mediated amplification assay versions for detection of hepatitis B virus, hepatitis C virus, and human immunodeficiency virus Type 1 in blood donors

Abstract: More efficient target capture chemistry in the new TMA assay version significantly improved sensitivity and diminished variability in detecting HBV strains of various genotypes. We recommend a triplicate ID-NAT repeat test strategy to eliminate discriminatory tests on false-non-repeat-reactive (anti-HBc-nonreactive) donations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(79 citation statements)
references
References 27 publications
2
74
1
2
Order By: Relevance
“…RDEs and residual transmission risk for ID‐, MP8‐, and MP16‐NAT were calculated using an RDE modeling spreadsheet with the following input parameters: The number of screened donations from lapsed or repeat (or lapsed plus repeat) donors during the study period; The number of HCV infections in the screened lapsed and/or repeat donations identified by ID‐NAT or anti‐HCV serologic screening or both; The harmonic mean of the interdonation intervals preceding detected infections; HCV viral doubling time of 0.45 days; 50% minimum infectious dose (MID 50 ) of 3.16 virions; ID‐NAT 95 and 50% limits of detection of 16.3 and 2.2 HCV copies/mL, respectively; Transfused plasma volume of 20 mL for RBC units and 200 mL for fresh‐frozen plasma (FFP) units, assuming that all infectivity is attributable to plasma viremia. …”
Section: Methodsmentioning
confidence: 99%
“…RDEs and residual transmission risk for ID‐, MP8‐, and MP16‐NAT were calculated using an RDE modeling spreadsheet with the following input parameters: The number of screened donations from lapsed or repeat (or lapsed plus repeat) donors during the study period; The number of HCV infections in the screened lapsed and/or repeat donations identified by ID‐NAT or anti‐HCV serologic screening or both; The harmonic mean of the interdonation intervals preceding detected infections; HCV viral doubling time of 0.45 days; 50% minimum infectious dose (MID 50 ) of 3.16 virions; ID‐NAT 95 and 50% limits of detection of 16.3 and 2.2 HCV copies/mL, respectively; Transfused plasma volume of 20 mL for RBC units and 200 mL for fresh‐frozen plasma (FFP) units, assuming that all infectivity is attributable to plasma viremia. …”
Section: Methodsmentioning
confidence: 99%
“…Multiple replicate ID‐NATs were performed in a large number of donor samples from this latter group to determine the proportion in whom low‐level viremia (indicative of so‐called “occult HCV infection”) was demonstrable. By comparing the viral concentrations in the three infection stages against HCV‐RNA reference panels and infectivity standards, the probability of HCV transmission by blood transfusion could be estimated. This knowledge is a necessary component for comparing the efficacy of serologic testing and ID‐NAT in preventing HCV transmission risk, as has been done using data from an international surveillance study …”
mentioning
confidence: 99%
“…They argue that the cause of such questionable results is due to FP IR-NAT, OBI, or window-period donations. In a study performed on Polish donors, it was shown that from 9,980 first-time donors, the IR rate with the Ultrio Plus assay on the Tigris was 0.85, and 0.63% were RR whereas 0.22% were non-RR, and the calculated specificity of initial screening result lay around 99.77% [10]. These authors calculated a 100% specificity with a triplicate ID NAT repeat-testing strategy to eliminate discriminatory tests on false non-RR anti-HBc nonreactive donations.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, many testing centers have a policy to not use IR donations for transfusion, even though it is known that the vast majority of these donations are FP. This can lead to the loss of valuable donations and needless donor deferrals, so many testing centers around the world including ours have now implemented replicate (duplicate, triplicate, or greater) repeat test strategies on the primary screening tube or sometimes from the fresh frozen plasma (FFP) collected from respective donations [5, 10]. This replicate repeat testing helps to identify low-viral-load samples which may be below the sensitivity limit of the quantitative NAT assays often used for confirmation.…”
Section: Discussionmentioning
confidence: 99%